Phytochemical Profiling and Bioactivity Assessment of Methanolic Leaf and Root Extracts of Dillenia suffruticosa: Unveiling Antioxidant Potential and Cytoprotective Effects in HUVECs - Izzy Nurathirah, Malek; Zunika, Amit; Dayang Erna Zulaikha, Awang Hamsin; Angela, Siner; Asheila, Meramat; Majed Ahmed, Al-Mansoub
Dillenia suffruticosa (Dilleniaceae) is a medicinal plant indigenous to Southeast Asia, including Malaysia. Traditionally, it has been used to treat ailments such as fever, rheumatism, and inflammation. This study aimed to evaluate the phytochemical composition, antioxidant activity, and cytoprotective potential of methanolic extracts derived from the leaves and roots of D. suffruticosa. The extracts were subjected to gas chromatography-mass spectrometry (GC–MS) for volatile constituent profiling. Antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and the ferric reducing antioxidant power (FRAP) assay. Cytoprotective effects were evaluated in human umbilical vein endothelial cells (HUVECs) using the Cell Counting Kit-8 (CCK-8) assay across a range of concentrations. GC–MS analysis revealed the presence of fatty acids, phytosterols, and phenolic derivatives, with compositional differences observed between the two extracts. Both methanolic leaf and root extracts demonstrated comparable antioxidant activity; however, the root extract exhibited a slightly stronger free radical scavenging effect (IC₅₀: 3.62 ± 0.10 µg/mL) and higher FRAP value (207.63 ± 4.65 nmol Fe²⁺ eq./mg) than the leaf extract (IC₅₀: 4.79 ± 0.04 µg/mL; FRAP: 194.18 ± 3.64 nmol Fe²⁺ eq./mg). The CCK-8 assay showed that both extracts maintained cell viability above 70% at concentrations up to 50 µg/mL. These findings suggest that both leaf and root extracts of D. suffruticosa are rich in antioxidant compounds and exhibit promising cytoprotective effects in HUVECs. Further studies are underway to validate their bioactivity and explore their therapeutic potential in inflammation-associated vascular disorders.